Implementasi Black Box Testing Pada Aplikasi Pemesanan Makanan - Hardiansyah; Meri Hendayani; Ian Amukti Herlambang; Andhika Nove Rezki; Aries Saifudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
E-Menu's application is an application created to make it easier for customers to order food, so they can monitor the status of orders and queues. Before this application is used by the customer, testing is needed to anticipate system failure or the system does not run according to the flow that has been made, therefore testing is carried out using the method chosen, namely Black Box Testing. The object of testing this application uses the web, the number of modules tested is 2, namely the Menu Module for ordering and the Kitchen Module for processing orders, where each module is tested using the equivalence partitions technique, namely testing based on input data from each form in the application. Each input menu is tested and grouped according to its behavior, regardless of whether the results match or not. After examining all the features contained in the application, it can be concluded that the E-Menu application did not find any functional errors. So that the EMenu's application can run well and is ready to be used by customers and the kitchen.